Online theological education within the South African context - Knoetze, Johannes J. (HTS teologiese studies, 2022)
This article presents the results of an empirical research study conducted at the Faculty of Theology and Religion at the University of Pretoria on students’ experiences of online theological education during the outbreak of the coronavirus disease 2019 (COVID-19) pandemic between 2019 and 2020. Particular attention is given to the context of higher education in South Africa as a background to the research. The article discusses students’ views and experiences of the different modes of teaching, namely, face-to-face, online, and hybrid or blended teaching. After discussing the different modes of teaching, some of the challenges experienced in online learning are explored, and finally, several recommendations are proposed for the improvement of theological education. The article concludes with the finding that the current infrastructure in South Africa is sufficient to make online education sustainable. Within the present South African context, it might also be the only viable option to ensure access to higher education for students. The study also found that the current theological students prefer online or at least blended methods of theological education for different reasons mentioned in the article.Contribution: Although there are still some challenges to online theological education, the current infrastructure in South Africa is sufficient to make online education sustainable. The article promotes multi-, inter-, and transdisciplinary aspects of studies in the international theological arena.